SimAffling um ambiente computacional para suporte e simulação do processo de DNA shuffling - Cheung, Luciana Montera (Universidade Federal de São Carlos, 2008)
The Molecular Evolution of the living organisms is a slow process that occurs over the years producing mutations and recombinations at the genetic material, i.e. at the DNA. The mutations can occur as nucleotide remotion, insertion and/or substitution at the DNA chain. The Directed Molecular Evolution is an in vitro process that tries to improve biological functions of specific molecules producing mutations at the molecule s genetic material, mimicking the natural process of evolution. Many technics that simulate in vitro molecular evolution, among them the DNA shuffling, have been used aiming to improve specific properties of a variety of commercially important products as pharmaceutical proteins, vaccines and enzymes used in industries. The original DNA shuffling methodology can be sumarized by the following steps: 1) selection of the parental sequences; 2) random fragmentation of the parental sequences by an enzyme; 3) repeated cycles of PCR (Polymerase Chain Reaction), in order to reassemble the DNA fragments produced in the previous step; 4) PCR amplification of the reassembled sequences obtained in step 3). The DNA shuffling technic success can be measured by the number of recombinat molecules found at the DNA shuffling library obtained, since these recombinant molecules potentially have improved functionalities in relation to their parent since their sequence may accumulate beneficial mutations originated from distinct parent sequences. Nowadays some few models can be found in the literature whose purpose is to suggest optimization to this process aiming the increase of the genetic diversity of the DNA shuffling library obtained. This research work presents a comparative study of four models used to predict/estimate the DNA shuffling results. In addition a computational tool for simulating the DNA shuffling proccess is proposed and implemented in an environment where other functionalities related to the analyses of the parental sequences and the resulting sequences from the DNA shuffling library is also implemented.
Keywords: Biotecnologia; Simulação (Computadores); Evolução in vitro; DNA shuffling; Modelos de predição; Bioinformática; Biologia computacional; Computational simulation; In vitro evolution; DNA shuffling; Predicting models; Computational biology; Bioinformatics; NAO CATEGORIZADO